2015
DOI: 10.5603/aa.2015.0013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of up-to-date studies investigating effects of physical rehabilitation on traditional and novel biochemical parameters in PAD patients with intermittent claudication: a review

Abstract: Peripheral arterial disease severity ranges from asymptomatic (Fontaine stage I) through intermittent claudication (Fontaine stage II) to critical ischaemia (stage III and IV). Supervised exercise training is the main therapy used

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…14 However, less attention has been paid to whether SET can also impact on the CV risk profile of these patients. 15 Interestingly, one small retrospective study has shown that SET significantly altered CV morbidity and mortality in 64 patients completing SET compared with those who did not. 16 The primary driver behind this observation remains unclear, but the impact of exercise on traditional CV risk factors, and therefore risk of future morbidity and mortality, has already been established in patients presenting with similar CV risk profiles.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, less attention has been paid to whether SET can also impact on the CV risk profile of these patients. 15 Interestingly, one small retrospective study has shown that SET significantly altered CV morbidity and mortality in 64 patients completing SET compared with those who did not. 16 The primary driver behind this observation remains unclear, but the impact of exercise on traditional CV risk factors, and therefore risk of future morbidity and mortality, has already been established in patients presenting with similar CV risk profiles.…”
Section: Introductionmentioning
confidence: 99%